Uso de diferentes metodologias para secagem integral de pitaya vermelha (Hylocereus costaricensis) e seus impactos nos compostos bioativos - Oliveira, Igor Augusto Gonçalves de (2024)
The growth of fruit cultivation in Brazil has boosted the market for exotic fruits, such as pitaya (Hylocereus sp.), due to its functional and sensory characteristics. With its sweet and smooth pulp, pitaya can be consumed fresh or used in the development of new industrial products and in the production of natural dyes. Drying is crucial to preserve fruits with high water content (>80%), inhibiting microbial growth and enzyme activity. Employing appropriate drying methodologies is essential to preserve the product's properties. Drying pitaya (Hylocereus sp.) fruits to obtain powder offers several advantages and helps preserve the health-promoting compounds present in this fruit. This study aimed to evaluate the integral drying process of pitaya fruits (Hylocereus costaricensis) using spray dryer and refractance window methodologies, investigating the effects of these techniques on the final products. When using spray dryer, the effect of four independent variables was verified: drying air temperature (°C); drying air flow rate (m³/min); maltodextrin content (%) and feed flow rate (L/h).For refractance window method, the impact of temperature (°C) and time (min) was evaluated. The response variables analyzed for both methodologies were: final moisture, total phenolic content, total flavonoid content, total titratable acidity, ascorbic acid content, betalain content and color. For the spray dryer, the powder yield obtained was also analyzed. Spraydrying method resulted in pitaya powders with a light pink color due to the addition of maltodextrin and low moisture content (less than 5%). Better results were obtained by reducing the temperature and maltodextrin content, but the carrier agent was needed to obtain suitable material for analysis. The use of the refractance window showed the best overall results, preserving phenolic compounds, flavonoids, acidity and color compared to fresh fruit, although with a higher final moisture content. Furthermore, this method is economical, requiring less investment and eliminating the need to add a carrier agent, making it an excellent option for drying pitaya even at low temperatures.